2010
DOI: 10.1007/s13197-010-0201-3
|View full text |Cite
|
Sign up to set email alerts
|

Stability and transformation of major flavonols in onion (Allium cepa) solid wastes

Abstract: Onion solid wastes were analysed using HPLC and LC / MS and the major polyphenols detected were quercetin, quercetin 4′-O-glucoside, accompanied by protocatechuic acid and a benzofuranone derivative. The latter two compounds have been demonstrated as some of the degradation products that might arise as a result of peroxidase-mediated decomposition of quercetin. These four substances, along with two principal enzymes implicated in flavonols breakdown, β-glycosidase and peroxidise, were monitored throughout an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…Figure 1 illustrates the structures of quercetin aglycone, which lacks a sugar moiety, and of quercetin-β-glucoside, which has been reported to be contained mainly in onions. 14 , 15
Figure 1 Structure of quercetin aglycon ( A ), and quercetin-4ʹ-O-β-D-glucoside ( B ).
…”
Section: Chemical Structure and Dietary Source Of Quercetinmentioning
confidence: 99%
“…Figure 1 illustrates the structures of quercetin aglycone, which lacks a sugar moiety, and of quercetin-β-glucoside, which has been reported to be contained mainly in onions. 14 , 15
Figure 1 Structure of quercetin aglycon ( A ), and quercetin-4ʹ-O-β-D-glucoside ( B ).
…”
Section: Chemical Structure and Dietary Source Of Quercetinmentioning
confidence: 99%
“…The outer dry layers of onion bulbs contain a peculiar variety of polyphenols, many of them considered to derive from quercetin and quercetin glucosides, upon the action of peroxidase (LY et al, 2005;RAMOS et al, 2006;KHIARI & MAKRIS, 2012). The chromatogram of the extract obtained at 40 °C, which was monitored at 290 nm, revealed the presence of 5 major peaks accompanied by several minor substances.…”
Section: Polyphenolic Compositionmentioning
confidence: 99%
“…Among others, the dried outer skin of onions ( Allium cepa L.), representing the waste of onion consumption and processing, contains a multitude of colored bioactive phenolics, some of which are absent in the edible part of the vegetable [15,16,17]. In depth investigations at a molecular level have revealed that quercetin and its glucosides are the most abundant phenolics in onion outer dry layers, which explains the strong antioxidant effects of the resulting extracts [18,19,20].…”
Section: Introductionmentioning
confidence: 99%